Does Green Product Consumption Gendered? Investigating Among Millennials in an Emerging Market - Setyawan, A; Noermijati, N; Sunaryo, S; Aisjah, S (KnE Social Sciences, 2018)
The purpose of this study is to understand the difference in consumption patterns of green products among millennials based on a gender perspective. The marketing of these eco-friendly products to the millennials is interesting to be discussed in terms of sustainability. The sustainability is seen not only in the eco-friendly products but also from the consumers’ side, as millennials are potential consumers in the present and future. A detailed marketer’s understanding of millennials’ consumption patterns based on gender will provide an insight into appropriate marketing strategies in the emerging market context. To meet these objectives, 326 millennials were included as respondents in the survey conducted by the researchers. The results of the analysis on the whole sample indicated that the millennials’ intention of purchasing eco-friendly products is positively influenced by their attitudes toward green products, subjective norm and perceived behavioral control. Although the intention of purchasing green products between the male and female sample groups showed no different pattern, the attitude variable did not show any effect on the intention of purchasing green products in either men and women. Keywords: green product, millennials, gender differences, emerging market, purchase intention